2020
DOI: 10.1101/2020.05.19.103440
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenomic profiling of ammonia- and methane-oxidizing microorganisms in a Dutch drinking water treatment plant

Abstract: Highlights 10• Microbial distribution was mainly influenced by sampling location within the DWTP.• Clade A comammox Nitrospira were the most abundant nitrifying guild in samples from the primary sand filter, while clade B dominated in samples from wall biofilm and the secondary filter.• A novel methanotrophic bacterium affiliated with the Methylophilaceae family comprised 15 the largest bacterial fraction in the primary sand filter. AbstractElevated concentrations of ammonium and methane in groundwater can cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 124 publications
(104 reference statements)
1
6
0
Order By: Relevance
“…Tatari et al (2017) reported a high abundance of Nitrospira (5−10% of the total community) consistently in RSF filters and up to 2 to 4 orders of magnitude more abundant than Nitrobacter and canonical AOBs, respectively. The high abundance of Nitrospira in nitrifying guilds is also reported by other studies (Poghosyan et al 2020).…”
Section: Rapid Sand Filtrationsupporting
confidence: 87%
See 4 more Smart Citations
“…Tatari et al (2017) reported a high abundance of Nitrospira (5−10% of the total community) consistently in RSF filters and up to 2 to 4 orders of magnitude more abundant than Nitrobacter and canonical AOBs, respectively. The high abundance of Nitrospira in nitrifying guilds is also reported by other studies (Poghosyan et al 2020).…”
Section: Rapid Sand Filtrationsupporting
confidence: 87%
“…It was shown that the biological nitrification process is responsible for the reduction of the ammonia concentration in water in RSF filters (Oh et al 2018;Poghosyan et al 2020). The consistency of spatial dissimilarity of the ammonium removal capacity with the spatial heterogeneity of nitrifying guilds in RSF filters further supports the above hypothesis (Lee et al 2014).…”
Section: Rapid Sand Filtrationmentioning
confidence: 54%
See 3 more Smart Citations